2012
DOI: 10.1093/cid/cis406
|View full text |Cite
|
Sign up to set email alerts
|

HIV Status, Burden of Comorbid Disease, and Biomarkers of Inflammation, Altered Coagulation, and Monocyte Activation

Abstract: These data suggest that ongoing HIV replication and immune depletion significantly contribute to increased prevalence of elevated biomarkers of inflammation, altered coagulation, and monocyte activation. This contribution is independent of and in addition to the substantial contribution from comorbid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
200
2
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(220 citation statements)
references
References 38 publications
11
200
2
7
Order By: Relevance
“…We also collected information about hepatitis C, coronary artery disease, and comorbidities associated with cardiovascular disease, including hypertension, hyperlipidemia, and diabetes mellitus, as these conditions have been shown to be associated with increased risk of inflammation. 28,[38][39][40][41] Medical comorbidities were defined by inclusion as an active problem in the electronic medical record. Serum was collected for biomarker quantification, and each woman underwent a physical-function assessment as described below.…”
Section: Population Enrolledmentioning
confidence: 99%
See 2 more Smart Citations
“…We also collected information about hepatitis C, coronary artery disease, and comorbidities associated with cardiovascular disease, including hypertension, hyperlipidemia, and diabetes mellitus, as these conditions have been shown to be associated with increased risk of inflammation. 28,[38][39][40][41] Medical comorbidities were defined by inclusion as an active problem in the electronic medical record. Serum was collected for biomarker quantification, and each woman underwent a physical-function assessment as described below.…”
Section: Population Enrolledmentioning
confidence: 99%
“…Several studies have reported associations between higher inflammatory biomarker levels, including interleukin-6 (IL-6), high-sensitivity C-reactive protein (CRP), hyaluronic acid (HA), D-dimer, soluble CD14 (sCD14), and soluble tumor necrosis factor receptor-1 (sTNFR1) and sTNFR2, and increased mortality in ART-treated individuals. [23][24][25][26] Higher levels of inflammatory and coagulation biomarkers, such as IL-6, D-dimer, sCD14, and CRP, are seen in HIV-infected individuals compared to HIV-uninfected controls, despite treatment with ART and adjustment for other comorbidities 27,28 ; however, one study suggested that these elevated biomarker levels in ART-treated individuals were seen primarily in those with low CD4 counts or elevated HIV viral loads. 28 A recent study of HIV-infected individuals found that poor physical function was associated with immune activation and increased levels of IL-6.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relative contribution of HIV-infection and HIV-related factors such as inflammation, immune activation and altered coagulation to the development of different comorbidities in aging individuals is still inconclusive. Other risk factors, life style factors or the use of antiretroviral drugs may contribute to excess morbidity [2,8,[11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This activation leads to immune deficiency through the destruction of target cells, and also induces some other pernicious consequences, such as low thymic output, lymphoid tissue fibrosis and T-and B-cell dysfunction. Other more long-term effects are represented by inflammation, tissue damage and coagulopathy, including an increase in non-AIDS morbidity and mortality [3]. This is what the natural history of HIV would be without antiretroviral (ARV) drugs, which target several steps in the HIV lifecycle.…”
mentioning
confidence: 99%